Epidemiology of small-bowel obstruction beyond the neonatal period. Issue 3 (July 2016) - Houben, Christoph H.; Pang, Kristine K.; Mou, Wai Cheung; Chan, Kin Wai; Tam, Yuk Him; Lee, Kim Hung
Abstract : Background: The aim of this study was to evaluate the etiologies causing intestinal obstruction beyond the neonatal period. Patients and methods: An observational study was conducted on children between 1 month and 17 years of age who underwent surgery for small-bowel obstruction (SBO) at this tertiary referral center between 1 January 2004 and 31 December 2013. Results: In total, 133 patients (38 female) with a median age of 3.4 (range 0.16–15.8) years were included in the study group. Forty-four patients (18 female) had intussusception, of whom seven presented with a pathological lead point. Thirty-nine individuals (12 female) had a postoperative SBO. The median formation time for the SBO was 1.75 years, and neonatal anomalies represented the most frequent cause of initial surgery. Primary SBO with no previous surgery was observed in 30 children (eight girls), including 12 (9%) with Meckel's diverticulum, nine (7%) with congenital bands, and three (2%) with bezoars. Twenty patients (15%), all boys, presented with an irreducible inguinal hernia. During the surgery, a total of 43 (32%) patients underwent bowel resection or enterotomy. Five patients (3.8%) died, four as a result of sepsis and one following parenteral nutrition-related liver failure. Conclusion: Nearly a quarter of this cohort had a primary SBO. SBO in children is more prevalent among boys (M : F ratio, 2.5 : 1). Intussusception, postoperative adhesions, and irreducible inguinal hernias are the most common pathologies for SBO, followed by Meckel's diverticulum and congenital adhesive bands.